ANALYSIS OF STRUCTURE AND TEXTURE OF THE TEXT AS A REVIEW THE WORTHINESS OF A CHILD'S FABLE SERIES OF KESETIAAN MERPATI BY M. SYAFII MASYKUR - Juni Mahsusi (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2022)
This research was intended to identify the sctructure and texture of the text in a child’s story Kesetiaan Merpati by M. Syafii Masykur in addition to reviewing the language worthiness which is used by children under five years of age. The design of this research was qualitative descriptive research using the discourse analysis approach. The source of data in this research was the children's book story Kesetiaan Merpati, the data from this research was a lingual unit of words, clauses, or sentences found in children’s book story Kesetiaan Merpati. The data was collected by using the responsive technique and note-taking technique. To fulfill the aim of this research the data was taken by using a criterion-based sampling technique. The data were analyzed by using the distributional method and interactive analysis, which were data collection, data reduction, data presentation, deduction, and verification. The research found in the text structure of children's story Kesetiaan Merpati, there were orientation, complications, evaluation, resolution, and coda. Meanwhile, textual texture in the children’s story Kesetiaan Merpati consisted of grammatical and lexical. The narration of Kesetiaan Merpati found 45 grammatical errors; among these were ineffective sentence in 5 sentences, infrequent punctuation in 4 sentences, uneconomical word as 4, infrequent use of words as 4, the error of phonology as 3, the error of morphology as 1, the error of conjunction as 3, double subject as 2, the error of preposition as 1, the negative clause as 2, vocabulary as 8, nominalization as 6, technique term as 2 and the type of sentence used were paratactic and hypotactic complex. Hereinafter, on lexical of narration in 56 sentences. From the grammatical mistaken identification of the book story Kesetiaan Merpati by M. Syafii Maskur, it was not worthy to be given to a child under 5 years of age. This was seen in the many grammatical errors of a vocabulary that is difficult and uneasily understood by children of that age, as well as the clauses and metaphors.